The Indonesian Version of the Cooperative and Competitive Personality Scale: Psychometric Properties Examination Among University Students in West Java - Purnama, Chandra Yudistira; Wilis Srisayekti; Efi Fitriana (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
Understanding and accurately measuring cooperative and competitive behaviour is essential for effectively predicting and applying these traits across various fields. This study aimed to adapt the Cooperative and Competitive Personality Scale (CCPS) for use in Indonesia and evaluated its psychometric properties. The Indonesian CCPS was adapted through translation and back-translation, then tested on 720 participants alongside the Big Five Inventory-50, Prosocial Scale for Adults and Prosocial Tendencies Measure. The results showed α=0.934; ω=0.933 for the cooperative, and α=0.884; ω=0.831 for the competitive, and strong test-retest correlations (r=0.978 for cooperative, r=0.984 for competitive). The findings demonstrate that the Indonesian CCPS is a valid and reliable instrument with strong psychometric properties. The findings help researchers and practitioners identify cooperative and competitive behaviour across contexts. In addition, these findings support the use of CCPS to design interventions to enhance teamwork and healthy competition. Keywords: cooperative and competitive personality scale; factor analysis; Indonesian adaptation; invariance; psychometric evaluation